2014
DOI: 10.1016/j.cplett.2014.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Photoswitching of the spin crossover polymeric material [Fe(Htrz)2(trz)](BF4) under continuous laser irradiation in a Raman scattering experiment

Abstract: Photoswitching of the [Fe(Htrz) 2 (trz)](BF 4) spin crossover polymeric material has been investigated by means of confocal Raman spectroscopy upon continuous laser irradiation outside and inside its thermal hysteresis loop. In both cases, the evolution of HS and LS Raman marker bands show that light excitation can trigger the LS to HS transition, but the long-lived HS state can be populated only within the hysteresis loop. Local sample heating can explain this light-induced effect leading to a narrowing of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 35 publications
(57 reference statements)
1
27
0
Order By: Relevance
“…Note that bidirectional photo-switching inside the thermal hysteresis using pulsed nanosecond laser excitation was first reported for the SC sample [Fe(pyrazine)Pt(CN) 4 ], [35] and later on other type of SC solids, [36] using Raman spectroscopy.W hile there is no doubt about the physical mechanism of the LS to HS photo-transformation, the reverse process inside the hysteresis is still disputable.The reverse process feeds into the healthy debate,w hich was reignited recently by photocalorimetric measurements [37] under pulse laser on the [Fe-(pyrazine)Pt(CN) 4 ]S Cs ample,l eading to ac ontroversy.O f course,t hese results should be confirmed by other investigations,capitalizing as in Ref. [37],onthe remarkable advances of the last two decades,i nt he chemical synthesis of high quality single crystals, [3,[38][39][40][41] combined with technological advances in experimental techniques (ultra-fast photo-crystallography, [42][43][44] time-resolved optical experiments [27,45] ), and methods of visualization at the nanoscale. [46] In conclusion, we have experimentally shown that modulation of aw eak intensity of light at as uitable frequency could reversibly control the spin transition in the thermal hysteresis interval.…”
Section: Angewandte Chemiementioning
confidence: 66%
“…Note that bidirectional photo-switching inside the thermal hysteresis using pulsed nanosecond laser excitation was first reported for the SC sample [Fe(pyrazine)Pt(CN) 4 ], [35] and later on other type of SC solids, [36] using Raman spectroscopy.W hile there is no doubt about the physical mechanism of the LS to HS photo-transformation, the reverse process inside the hysteresis is still disputable.The reverse process feeds into the healthy debate,w hich was reignited recently by photocalorimetric measurements [37] under pulse laser on the [Fe-(pyrazine)Pt(CN) 4 ]S Cs ample,l eading to ac ontroversy.O f course,t hese results should be confirmed by other investigations,capitalizing as in Ref. [37],onthe remarkable advances of the last two decades,i nt he chemical synthesis of high quality single crystals, [3,[38][39][40][41] combined with technological advances in experimental techniques (ultra-fast photo-crystallography, [42][43][44] time-resolved optical experiments [27,45] ), and methods of visualization at the nanoscale. [46] In conclusion, we have experimentally shown that modulation of aw eak intensity of light at as uitable frequency could reversibly control the spin transition in the thermal hysteresis interval.…”
Section: Angewandte Chemiementioning
confidence: 66%
“…Fe(II) complexes represent the most numerous and remarkable family of SCO materials, matching all these requirements [7,8]. Several materials exhibit room temperature switchability [9] and ultra-fast light controlled responses [10][11][12][13][14]. In addition to their intrinsic properties, these SCO materials can be also used as probes to switch a second property in a hybrid multicomponent system [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Of course, these results should be confirmed by other investigations, capitalizing as in Ref. , on the remarkable advances of the last two decades, in the chemical synthesis of high quality single crystals, combined with technological advances in experimental techniques (ultra‐fast photo‐crystallography, time‐resolved optical experiments), and methods of visualization at the nanoscale …”
Section: Figurementioning
confidence: 52%